Evaluation of radiation exposure of medical staff during CT-guided interventions - Rathmann, Nils-Andreas; Diezler, Patricius; Weiß, Christel; Kostrzewa, Michael; Sadick, Maliha; Schönberg, Stefan; Diehl, Steffen J. (Journal of the American College of Radiology, 2015)
The purpose of this prospective study was to investigate absolute radiation exposure values and factors that influence radiation exposure of interventionists during CT-guided interventions (CTGIs). To our knowledge, no data exist regarding the radiation dose to which the interventionist is exposed during these procedures. Absolute radiation dose values from a total of 131 CTGIs were analyzed. Radiation dose values were collected by thermoluminescent dosimeters that were positioned above the lead protection being worn, on the forehead, thyroid, chest, gonads, and right and left hand and foot. The radiation doses were analyzed with respect to the experience level of the person performing the procedure, the degree of difficulty measured on a 4-point Likert scale, the lesion size measured on a 3-point Likert scale, and the CT system used. Median whole-body dose was 12 μSv. With the exception of the forehead, all whole-body radiation doses were statistically significantly lower in CTGIs performed using the modern dual-source CT system compared with the 16-slice multi-detector CT. For CTGIs rated as more complex, the radiation exposure of the radiologist performing the procedure was statistically significantly higher, with the exception of the left hand. A statistically significantly lower median whole-body dose was measured for inexperienced compared with experienced radiologists. However, a few dose measurements of more than 1 mSv were found at the right hand. Radiation exposure measured during CTGIs is low (<50 μSv). Because the radiation dose was higher in more-complex interventions and for 16-slice multi-detector row CT, inexperienced radiologists should focus on less-complex procedures.